2014
DOI: 10.1007/s12020-014-0358-z
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension and Hashimoto’s thyroiditis: does a relationship exist?

Abstract: Several studies examined the possibility that idiopathic pulmonary hypertension is related to thyroid autoimmune diseases. The aim of our study was to highlight the possible correlations between the pulmonary hypertension and Hashimoto's thyroiditis (HT). A total of 93 patients were enrolled, 70 suffering from HT in euthyroidism state and 23 controls. All underwent anthropometric [weight (Kg); height (m); Body Mass Index (Kg/m(2)): waist circumference (cm)] and biochemical [fasting blood glucose (mg/dl), TSH (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…Several studies have examined the relationship between idiopathic pulmonary hypertension with autoimmune thyroid disease. According to Ciccone et al [43], it was demonstrated that patients with Hashimoto's thyroiditis did not show significant pulmonary hypertension compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the relationship between idiopathic pulmonary hypertension with autoimmune thyroid disease. According to Ciccone et al [43], it was demonstrated that patients with Hashimoto's thyroiditis did not show significant pulmonary hypertension compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, only one previous study investigated the association between PH with FT 3 and FT 4 in euthyroid patients. Ciccone et al [12] enrolled 93 euthyroid patients, 70 suffering from Hashimoto's thyroiditis and 23 controls. They demonstrated PASP were not independently related to FT 3 , FT 4 , or TSH in this population.…”
Section: Discussionmentioning
confidence: 99%
“…However, Sugiura et al [11] showed that PASP was not significantly correlated with free triiodothyronine (FT 3 ) or FT 4 in patients with Graves' disease. And in patients with Hashimoto's thyroiditis, it was shown that FT 3 , FT 4 , or TSH was not independently related to PASP [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…În contrast, un studiu publicat in anul 2015 a concluzionat că pacienții cu tiroidită Hashimoto nu au prezentat hipertensiune pulmonară relevantă comparativ cu subiecții sănătoși (6).…”
Section: Prevalenţa Hipertensiunii Arteriale Pulmonare (Hap) La Pacieunclassified